A qualitative analysis of the barriers to antiretroviral therapy initiation among children 2 to 18 months of age in Swaziland. Issue 4 (2nd October 2017) - Ahmed, Charisse V; Jolly, Pauline; Padilla, Luz; Malinga, Musa; Harris, Chantal; Mthethwa, Nobuhle; Ba, Inessa; Styles, Amy; Perry, Sarah; Brooks, Raina; Naluyinda-Kitabire, Florence; Mamba, Makhosini; et al.
Abstract : HIV/AIDS remains one of the leading causes of death among children under 5 years old in Swaziland. Although studies have shown that early initiation of infants and children diagnosed with HIV on antiretroviral therapy (ART) significantly reduces mortality, many children do not initiate ART until the later stages of disease. This study was designed to collect qualitative data from mothers and caregivers of HIV-positive children to identify the barriers to ART initiation. Focus group discussion (FGD) sessions were conducted in siSwati between July and September 2014 among caregivers of aged children 2–18 months in Swaziland who did or did not initiate ART between January 2011 and December 2012 after HIV DNA PCR-positive diagnosis of the infants. Denial, guilt, lack of knowledge, tuberculosis (TB)/HIV co-infection, HIV-related stigma, lack of money, and distance to clinics were reported by the participants as barriers to ART initiation. The findings further revealed that non-initiation on ART was not linked to a negative perception of the treatment. Findings suggest a need to improve sensitivity among healthcare workers as well as education and counselling services that will facilitate the ART initiation process.